2013
DOI: 10.1097/prs.0b013e3182789ad4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Angiogenesis with Short-Term Immunosuppression Maintains Bone Viability in Rabbit Allogenic Knee Joint Transplantation

Abstract: Background Vascularized Composite Allotransplantation (VCA) has potential for reconstruction of joint defects, but requires life-long immunosuppression (IS), with substantial risks. This study evaluates an alternative, using surgical angiogenesis from implanted autogenous vessels to maintain viability without long-term immunotherapy. Methods Vascularized knee joints were transplanted from Dutch Belted donors to New Zealand White rabbit recipients. Once positioned and revascularized microsurgically, a recipie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…As hypothesized, the implantation of an autogenous AV‐bundle within the tibial allotransplant improved endosteal static and dynamic remodeling parameters, implying a successful promotion of new bone formation and improved bone remodeling in bone VCAs with an implanted recipient‐derived AV bundle. These results support our previous studies in orthotopic rat and rabbit knee joint and femoral transplantation . The benefits at 16 weeks were significant only on the deep (endosteal) cortical bone surface, demonstrating no effect of an intramedullary pedicle on periosteal circulation at that point in time.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As hypothesized, the implantation of an autogenous AV‐bundle within the tibial allotransplant improved endosteal static and dynamic remodeling parameters, implying a successful promotion of new bone formation and improved bone remodeling in bone VCAs with an implanted recipient‐derived AV bundle. These results support our previous studies in orthotopic rat and rabbit knee joint and femoral transplantation . The benefits at 16 weeks were significant only on the deep (endosteal) cortical bone surface, demonstrating no effect of an intramedullary pedicle on periosteal circulation at that point in time.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous research, we have used this same strategy to maintain bone and joint VCA viability, coupled with short‐term immunosuppression to maintain the allogeneic nutrient pedicle blood flow during autogenous vessel angiogenesis. We have demonstrated surgical angiogenesis to revascularize necrotic structural allografts, maintain viability and promote bone remodeling in rat and rabbit skeletal defect models without the need of long‐term immunosuppression . This report is a progression of our previous work.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Previous studies have demonstrated that bone VCAs may be maintained in small animal models without the need of long‐term IS by switching the circulation of the transplant from allogenic to autogenous vessels, enabled by implantation of an arteriovenous bundle (AV bundle) elevated from adjacent soft tissue and placed within the allotransplant. The allogenic nutrient vessels are repaired microsurgically at the same time, but only short‐term immunosuppression is used . The immunosuppressive period allows nutrient pedicle to maintain transplant blood flow and cell viability.…”
mentioning
confidence: 99%